A new model for tubular fluorescent lamps operated at high frequencies for dimmable applications - Wakabayashi, F. T.; Canesin, C. A. (IEEE, 2003)
This paper presents a new static model for tubular fluorescent lamps (T12 bulb) operated at high frequencies. The main goal of this paper is to investigate the effects of ambient temperature and nominal switching frequency of operation in the static characteristics of tubular fluorescent lamps. The methodology for obtaining the model is based on several two-dimensional mathematical regressions, used to provide the behavior of the fluorescent lamp according to different independent variables, namely: power processed through the lamp and ambient temperature. In addition, the proposed model can be easily converted to a lamp equivalent resistance model, which can be useful for ballast designers. Finally, the curves obtained using the new model are compared to the correspondent experimental data, in order to verify the accuracy of the proposed methodology.
Keywords: fluorescent lamp static model; high frequencies; dimmable applications